Determinanty polityki zarządzania majątkiem na przykładzie przedsiębiorstw przemysłu meblarskiego - Bober, Piotr; Sobolewski, Henryk ("The Determinants of the Policy of the Management the Property on Example the Enterprises of Furniture Industry", 2005)
On the basis of conducted researches we can draw a conclusions that are following:1) considered furniture companies changed the structure of overall property in favour of short-term property regardless of crucial motion of overall property with the acception of one of them, 2) quicker pace of increasing sales income (that in the long term means quicker increase of scale of production to assume that sale is inveriable) than pace of increasing overall property and especially than pace of increasing long-term property show about more effective usage, 3) Overwhelming share of tangible assets in long-term property shows that in this industry other elements of long-term property in increase scale of production are of no importance, 4) rising share of amount due in considered furniture companies in analised period is characterised for market economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 32-46